Epidemiologia e custos hospitalares de internações de pacientes com infecções de origem odontogênica em um hospital público de Belo Horizonte - Luciana Carvalho Soares Almeida (2023)
Introduction: Odontogenic Infection (IO) has its origin in the dental and supporting tissue, which in an eventual situation, can evolve into the underlying fascial spaces. The infectious process can evolve from a simple localized odontogenic infection to a severe maxillofacial infection, leading to serious complications. The epidemiology of OI is important for the development of prevention strategies, thus avoiding progression to serious complications and hospitalization. The resulting implications of OI continue to be a significant public health concern and this is not only due to its harmful potential for health, but also the considerable hospital financial burden linked to the treatment of these situations. Objectives: To analyze cases of infection of odontogenic origin in patients admitted to the Oral and Maxillofacial Surgery and Traumatology Sector of the Hospital Metropolitano Odilon Behrens (HMOB), in Belo Horizonte, Minas Gerais, Brazil. Materials and methods: Cross-sectional, analytical study, carried out through the collection of secondary data. A total of 530 medical records of patients hospitalized due to odontogenic infection at the HMOB between January 2018 and December 2022 were analyzed. The independent variables were age, gender, presence of comorbidity, municipality of residence, year, side of the face, etiology of infection, tooth affected and dental arch. The dependent variables consisted of a severity score constructed from the clinical management and hospitalization complications variables. In addition, information was collected on the number of days of hospitalization and the cost of hospitalizations. Descriptive static analyzes were performed and those that had a p<0.05 were included in the Poisson regression analysis with robust variance. Results: It can be seen that approximately 60.6% of the patients used at least one of the options for intraoral or extraoral drain. Ludwig’s Angina was identified in 7.4% of the sample. The year with the highest number of hospitalizations was 2022 (24.2%), in which they mostly occurred in the first quarter (28.9%), caused by infections that affected the right side (42.3%), the etiology of the majority of cases was caries (56.4%), the most affected tooth was the lower permanent molar (55.3%) and the mandible (88.7%). The mean length of stay was 6.9 days, and it was possible to see an increase in the mean length of stay over the years. The average number of antibiotics administered to patients was 2.2 and the total average cost of hospitalizations in the period between January 2018 and December 2022 was R$991.65. People aged over 60 years had a 19% greater severity than those aged 1 to 19 years. Regarding the year of hospitalization, those who were hospitalized in 2022 had a 13% more severe condition than patients hospitalized in 2018 and it was possible to observe evidence of a dose-response gradient When year and severity were related. Cases in which the involvement was bilateral were 38% more severe than when the involvement was on one side of the face; and the cases that affected the mandible were 17% more severe than when the maxilla was affected. Belo Horizonte was georeferenced based on the home addresses of patients in the city. The distribution of cases resulting from infection of odontogenic origin was homogeneous in the municipality. When analyzing the per capita Monthly income of households earning 2 minimum wages, the formation of highdensity clusters was observed in the Aparecida and Santa Mônica neighborhoods. Conclusion: It is concluded that most cases of hospitalization due to odontogenic infection were patients residing in the city of Belo Horizonte, the main cause was caries, the most affected teeth were permanent lower molars and involvement of the mandible. The adoption of preventive strategies and early intervention emerge as prominent approaches.